CONSIDERATIONS REGARDING EFFICIENT USE OF ABRASIVE MATERIAL IN WATER JET CUTTING - Aurel Perianu; Dumitru Mnerie; Gabriela Victoria Mnerie; Dan Ionescu (Nonconventional Technologies Review, 2020)
Abrasive Water jet cutting process fits in the category of unconventional dimensional processing technologies, based on the principle of erosion with complex fluid environments, kinetically activated. Currently, there are multiple researches for process optimization, especially taking into consideration the economic criteria, due to relatively higher costs present in the case of abrasive waterjet cutting. The paper presents a synthesis of a study started from research within the National R & D Institute for Welding and Material Testing - ISIM TIMIŞOARA, especially in the direction of increasing the efficiency of using the abrasive material associated with this cutting process. Several patented results regarding the recycling of used abrasive material in other fields are presented, as well as prospects for further research by studying other methods aimed at reducing costs without reducing the level of quality for abrasive water-jet cuts.